2020
DOI: 10.1109/access.2020.2970164
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Research on Traffic Conflicts Based on Intelligent Vehicles

Abstract: The traffic situation at an urban intersection is complicated, due to the numerous internal conflicts and all kinds of traffic accidents. With the objective of improving road safety, the automotive industry is moving toward intelligent vehicles. The major challenges are accurately perceiving the road traffic environment, detecting the potential traffic conflicts, and proposing the alternative driving strategies. This paper summarizes the existing researches on traffic conflicts from the perspective of intellig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 84 publications
1
37
0
1
Order By: Relevance
“…At the same time, the data from VISSIM is transferred to MATLAB, where the proposed algorithm is working and gives the result about the queue length. As shown in [12], the penetration rates may impose a great effect on the estimate accuracy and can be estimated by V2X [51]. Therefore, several penetration rate levels are validated in the simulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the data from VISSIM is transferred to MATLAB, where the proposed algorithm is working and gives the result about the queue length. As shown in [12], the penetration rates may impose a great effect on the estimate accuracy and can be estimated by V2X [51]. Therefore, several penetration rate levels are validated in the simulation.…”
Section: Resultsmentioning
confidence: 99%
“…It seems that the connected vehicles can provide some service for traffic states sensing when travelling on the road [11]. The connected vehicle can act as a mobile traffic information sensor [12,13]. In a mixed traffic scenario, the information from connected vehicle is used in delicate traffic models to estimate the traffic volume at the intersection [14].…”
Section: Introductionmentioning
confidence: 99%
“…Comfort and safety are important considerations in the automotive industry, 1,2 and the ride comfort and handling stability are direct manifestations of these two properties. Suspension systems are used to transfer forces and moments between the car body and the ground.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, one of the most important goals in the automotive industry has been to offer passengers the highest level of safety, comfort, and efficiency by partially or completely removing driving duties from humans. Advanced Driver Assistant System (ADAS) has become a research hotspot in the field of intelligent transportation; it not only improves the road capacity [1], but also ensures the safety of drivers and vulnerable road users to some extent [2,3]. Studies have shown that the active safety systems, such as adaptive cruise control, electronic stability control, or lane keeping assistant, which are already on the automotive market, can improve safety by decreasing the number of traffic accidents, among which the ACC helps a lot to reduce the driver's work intensity; an ACC equipped vehicle uses radar or other sensors that detect the distance and speed to other preceding vehicles (downstream vehicles) on the highway.…”
Section: Introductionmentioning
confidence: 99%